PSYCHOPATHOLOGICAL DIMENSIONS RELATED TO TOBACCO CONSUMPTION AMONG UNIVERSITY STUDENTS - Villar Hoz, Esperanza; Viñas Poch, Ferran; Juan Ferrer, Jaume; Caparrós Caparrós, Beatriz; Pérez Guerra, Isabel; Cornellá Canals, Montserrat (Anales de Psicología / Annals of Psychology, 2004)
The purpose of this study was to examine the relationship between psychological distress and tobacco consumption in a sample of 1.242 randomly selected university undergraduates. Results showed a significant, positive association between the participants’ psychopathological status and cigarette smoking. Moreover, findings demonstrated that tobacco consumption was also significantly related to the subjective perception of stressful life events, self-medication, and irregular eating behaviours. According to the self-medication hypothesis, data suggest that smoking helps smokers to cope with negative affect states, which should be considered in tobacco prevention and smoking cessation programs in order to enhance emotional control and coping strategies.